The Influence of Tourist Perceptions and Tourist Experiences on Positive Electronic Word of Mouth (e-WOM) in the Pantai Indah Kapuk Area as an Urban Tourist Attraction - Palupi, Putri Esthi; Juliana, Juliana; Hubner, Ira Brunchilda (Jurnal EMT KITA, 2025)
The growing phenomenon of sharing travel reviews online has become a key focus in urban tourism destination marketing. This study aims to analyze the influence of tourist perception and tourist experience on positive electronic word of mouth (e-WOM) regarding the Pantai Indah Kapuk tourist destination. The sample consists of 205 tourists who visited Pantai Indah Kapuk within the past year and are active social media users, selected using purposive sampling. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results indicate that both tourist perception and tourist experience have a positive and significant effect on positive e-WOM. Among the two, tourist experience emerged as the most dominant factor in encouraging positive e-WOM. The analysis using SEM-PLS revealed that both tourist perception (path coefficient = 0.232; p = 0.001) and tourist experience (path coefficient = 0.479; p = 0.000) positively and significantly influence positive e-WOM, with tourist experience as the most dominant factor. Theoretically, this study reinforces the application of the Theory of Planned Behavior in digital tourism contexts. The research is limited to one urban destination and respondents who are mostly young and active on social media. Future studies are recommended to cover broader destinations, include more diverse tourist segments, and apply a longitudinal design to capture behavioral dynamics over time These findings suggest that destination managers should focus not only on branding narratives but also on enhancing the overall tourist experience through improved facilities, engaging events, and effective social media engagement strategies.